Technical Efficiency of Cabbage Farming (Brassica oleracea) With Stochastic Frontier Analysis (SFA) Approach in Purwodadi - Pasuruan - Suaibatul Miskiyah; Syafrial Syafrial; Sujarwo Sujarwo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
This study was aimed to analyze the factors affecting the cabbage production, the level of technical efficiency of cabbage farming, the factors affecting technical inefficiency, and the profits of cabbage farming. The location was determined purposively on the basis that it is the center of vegetable cultivation. Â The respondents were 67 farmers chosen using the Yamane formula sampling technique. This research used frontier software 4.1 data analysis method with Maximum Likelihood Estimation (MLE) approach and Tobit regression. The results showed that land, labor, seeds, organic fertilizers, urea fertilizers, za fertilizers and npk fertilizers were real influential factors. Meanwhile, pesticides were insignificantly influenced. The mean technical efficiency in the research site was 0.903 for the distribution of technical efficiency, so that the cabbage production was rated as high efficiency. Age, education and credit access dummy contributed a major impact on technological inefficiency. The income from cabbage farming per planting season per hectare was Rp35,524,300 from cash costs and Rp31,051,800 from total costs.